2002
DOI: 10.1039/b200370h
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic devices fabricated in poly(methyl methacrylate) using hot-embossing with integrated sampling capillary and fiber optics for fluorescence detection

Abstract: High-aspect-ratio microstructures have been prepared using hot-embossing techniques in poly(methyl methacrylate) (PMMA) from Ni-based molding dies prepared using LIGA (Lithographie, Galvanoformung, Abformung). Due to the small amount of mask undercutting associated with X-ray lithography and the high energy X-ray beam used during photoresist patterning, deep structures with sharp and smooth sidewalls have been prepared. The Ni-electroforms produced devices with minimal replication errors using hot-embossing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 44 publications
2
86
0
1
Order By: Relevance
“…A mold insert for hot embossing was produced using the LIGA process. [43][44][45] The mold insert was used to hot emboss several microfluidic channels in polycarbonate substrates (Goodfellow, UK) using a PHI (City of Industry, CA) press equipped with a vacuum chamber. Inspection of SEM micrographs indicated that the sidewalls of the embossed channels were straight and smooth and contained the insert-defined channel width and height indicating minimal replication errors.…”
Section: Experimental Methods Cfpcr Device and Apparatusmentioning
confidence: 99%
“…A mold insert for hot embossing was produced using the LIGA process. [43][44][45] The mold insert was used to hot emboss several microfluidic channels in polycarbonate substrates (Goodfellow, UK) using a PHI (City of Industry, CA) press equipped with a vacuum chamber. Inspection of SEM micrographs indicated that the sidewalls of the embossed channels were straight and smooth and contained the insert-defined channel width and height indicating minimal replication errors.…”
Section: Experimental Methods Cfpcr Device and Apparatusmentioning
confidence: 99%
“…Current methods for fabrication of microfluidic devices include prototyping techniques (includes hot embossing, 55,56 injection molding, 57,58 and soft lithography 59 ) and direct fabrication techniques such as laser photoablation or laser micromachining, 60 photolithography/optical lithography 61 and x-ray lithography 62 ( Figs. 1 and 2).…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…In that regard, a good coating needs not only to effectively suppress the non-specific adsorption of biomolecules but also must show stability under prolonged rinsing and immersing with buffer which is commonly required in. This is believed to be useful for the design and development of PMMA-based microfluidic immunosensor and biosensors [22][23][24][25][26]. …”
Section: Introductionmentioning
confidence: 99%